2009
DOI: 10.1108/01437720910948429
|View full text |Cite
|
Sign up to set email alerts
|

Labor market outcomes of immigrants and non‐citizens in the EU

Abstract: PurposeThe purpose of this paper is to comparatively analyse the roles of foreign origin and citizenship in the labor markets of Eastern and Eestern Member States of the EU.Design/methodology/approachThe EU Survey of Income and Living Conditions is used to evaluate the roles of foreign origin and citizenship on employment and earnings using the standard Probit and OLS econometric models. The native/non‐native labor market divide is measured using Fairlie and Oaxaca‐Blinder decomposition techniques.FindingsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 31 publications
1
36
0
1
Order By: Relevance
“…There is a large body of literature providing robust evidence that ethnic and language minorities face various forms of labor market disadvantages in European labor markets; see Kahanec and Zaiceva (2009) the costs for employers of hiring a native relative to hiring an immigrant‖ and finds that negative effect of a strict EPL on employment and hiring rates is less pronounced for immigrants than for natives. The same argument, however, suggests that immigrants are more likely to accept informal jobs.…”
Section: Dependent Informality Rates By Worker and Job Characteristicmentioning
confidence: 99%
“…There is a large body of literature providing robust evidence that ethnic and language minorities face various forms of labor market disadvantages in European labor markets; see Kahanec and Zaiceva (2009) the costs for employers of hiring a native relative to hiring an immigrant‖ and finds that negative effect of a strict EPL on employment and hiring rates is less pronounced for immigrants than for natives. The same argument, however, suggests that immigrants are more likely to accept informal jobs.…”
Section: Dependent Informality Rates By Worker and Job Characteristicmentioning
confidence: 99%
“…One of the most intriguing questions about the post-enlargement migration wave from the Baltic countries is the behavior of Russian-speaking minorities, many of whom in Estonia and Latvia do not have citizenship; and hence, they are not covered by the free mobility provisions (see Kahanec and Zaiceva (2009) for a study on the citizenship effects on labor market outcomes in Europe).…”
Section: Demographics Of the Baltic Migrationmentioning
confidence: 99%
“…Studies have consistently found that recent immigrants continue to encounter significant barriers when searching for jobs in the labor market of their destination countries (Aydemir & Skuterud, 2005;Frenette & Morissette, 2005: Kahanec & Zaiceva, 2009Wald & Fang, 2009). Immigrant job search is a process of selecting different search methods that immigrants use to identify job opportunities and evaluate strategies for job success in their country of immigration (Greve, Salaff, & Chan, 2007).…”
Section: Introductionmentioning
confidence: 99%